2016
DOI: 10.1586/14737175.2016.1134324
|View full text |Cite
|
Sign up to set email alerts
|

Promoting recovery from ischemic stroke

Abstract: Over recent decades, experimental and clinical stroke studies have identified a number of neurorestorative treatments that stimulate neural plasticity and promote functional recovery. In contrast to the acute stroke treatments thrombolysis and endovascular thrombectomy, neurorestorative treatments are still effective when initiated days after stroke onset, which makes them applicable to virtually all stroke patients. In this article, selected physical, pharmacological and cell-based neurorestorative therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 129 publications
0
10
0
Order By: Relevance
“…It is now widely believed that several days after the onset of stroke is an appropriate time window for cell transplantation therapy. Based on the understanding of the time course of excitotoxicity, brain edema, inflammatory reaction, and trophic factor expressions, we and many others have typically transplanted cells at 7 days after stroke, at which point the extracellular glutamate has returned to lower levels, brain edema subsided, and the microenvironment in the post-stroke brain has entered into a pro-regeneration stage (Schmidt and Minnerup, 2016). Coincidentally, reported clinical trials with autologous MSCs have been limited by the time needed to expand cells to the point that an appropriate cell numbers are available, which normally takes several days or longer (Honmou et al , 2011; Lee et al , 2010).…”
Section: Timing Of Stem Cell Transplantationmentioning
confidence: 99%
“…It is now widely believed that several days after the onset of stroke is an appropriate time window for cell transplantation therapy. Based on the understanding of the time course of excitotoxicity, brain edema, inflammatory reaction, and trophic factor expressions, we and many others have typically transplanted cells at 7 days after stroke, at which point the extracellular glutamate has returned to lower levels, brain edema subsided, and the microenvironment in the post-stroke brain has entered into a pro-regeneration stage (Schmidt and Minnerup, 2016). Coincidentally, reported clinical trials with autologous MSCs have been limited by the time needed to expand cells to the point that an appropriate cell numbers are available, which normally takes several days or longer (Honmou et al , 2011; Lee et al , 2010).…”
Section: Timing Of Stem Cell Transplantationmentioning
confidence: 99%
“…In some trials, neural stem cell (NSCs) transplantation was used to treat stroke, and it was found that when the transplantation was conducted on the second day after onset, the number of surviving cells was greater compared with the transplantation done in the sixth week [ 111 ]. Taking into account the excitotoxicity, brain edema, inflammatory response, and the expression of nutritional factors and other factors, most researchers believe that 7 days after the onset of stroke is a better time for transplantation, because at this time the brain microenvironment has entered the stage of promoting regeneration [ 112 ].…”
Section: Applicationmentioning
confidence: 99%
“…The receptor for EPO is abundantly present within both central and peripheral nervous systems and plays a role in neural degenerative diseases by attenuating hypoxic insults [ 76 , 77 ]. Recombinant EPO has been successfully used in clinical trials to improve neurologic function following ischemic stroke in humans [ 78 , 79 ]. The neurotrophic properties of EPO make its use particularly attractive for CNI models of ED.…”
Section: New Molecular Targets For Neurogenic Edmentioning
confidence: 99%